2009
DOI: 10.3988/jcn.2009.5.1.39
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Erythropoietin in the Spinal Cord of Lewis Rats with Experimental Autoimmune Encephalomyelitis

Abstract: Background and PurposeaaErythropoietin (Epo), originally recognized for its central role in erythropoiesis, has been shown to improve the outcomes in patients with various neurological disorders. The aim of this study was to elucidate the Epo expression pattern in the spinal cords of Lewis rats with experimental autoimmune encephalomyelitis (EAE) and to assess the systemic effect of Epo during the course of EAE.MethodsaaWe used an EAE model induced in Lewis rats by immunization with myelin basic protein. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Following CNS injury, EPO is stimulated with hypoxia-inducible factors, and has been found to be activated and to protect neurons after ischemia-reperfusion injury in animal models [5, 52]. With the immunization of organ-specific antigens, semi-quantitative analysis has demonstrated that the expression of EPO is upregulated in the CNS [20] and in the PNS [36], which may contribute to the protection of neurons either by paracrine or autocrine mechanisms. Furthermore, EPO has been immune-detected in neurons, glial cells, and macrophages in EAE [20] and EAN [36] models.…”
Section: Protection Of Neurons By Epo In Neuroinflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…Following CNS injury, EPO is stimulated with hypoxia-inducible factors, and has been found to be activated and to protect neurons after ischemia-reperfusion injury in animal models [5, 52]. With the immunization of organ-specific antigens, semi-quantitative analysis has demonstrated that the expression of EPO is upregulated in the CNS [20] and in the PNS [36], which may contribute to the protection of neurons either by paracrine or autocrine mechanisms. Furthermore, EPO has been immune-detected in neurons, glial cells, and macrophages in EAE [20] and EAN [36] models.…”
Section: Protection Of Neurons By Epo In Neuroinflammationmentioning
confidence: 99%
“…With the immunization of organ-specific antigens, semi-quantitative analysis has demonstrated that the expression of EPO is upregulated in the CNS [20] and in the PNS [36], which may contribute to the protection of neurons either by paracrine or autocrine mechanisms. Furthermore, EPO has been immune-detected in neurons, glial cells, and macrophages in EAE [20] and EAN [36] models. In EAE models, there is no doubt that neurons and glial cells exhibit an increased immunoreactivity of EPO, but the influence of EPO on macrophages requires further analysis.…”
Section: Protection Of Neurons By Epo In Neuroinflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…This treatment caused a reduction in the clinical scores, a delay in the onset of the clinical signs, and a lower incidence of EAE [48]. In another study, EPO had the most pronounced effects on the clinical signs on EAE in rats, when the protein was administered prior to the onset of the clinical symptoms as compared to when the animals already had clinical signs at the onset of EPO administration [49]. Together, these observations suggest that the effects of Epobis on the progression of EAE could have been improved by administering the peptide earlier after immunization.…”
Section: Discussionmentioning
confidence: 99%